E-059 Versatile cerebrovascular platform for evaluation and development of thrombectomy technologies. (4th August 2020) - Liu, Y; Reddy, A; Cockrum, J; Gebrezgiabhier, D; Davis, E; Zheng, Y; Pandey, A; Shih, A; Savastano, L
Abstract : Introduction: Cerebrovascular test beds for large vessel occlusion (LVO) stroke are widely used to evaluate and develop new thrombectomy technologies and strategies. Most of the studies on test beds described the fabrication of the cerebrovascular phantoms but not the flow circuit and clot analogs, which are essential components to replicate LVO in patients with stroke. In addition, cerebrovascular phantoms are made from different materials and techniques and may result in different and biased testing results. However, such comparison has not been studied. We describe in detail the construction of a cerebrovascular test bed for stroke and compare the advantages and disadvantages of different types of cerebrovascular phantoms. Materials and Methods: The testing platform for thrombectomy was developed with three components: 1) cerebrovascular phantom, 2) hydraulic system, and 3) clot analogs. For the cerebrovascular phantom, patient-specific cerebrovasculature was reconstructed and three types of phantoms were fabricated: 3D-printed resin, glass, and silicone. For the hydraulic system, a syringe pump, tubing and variable flow resistors were connected to the phantoms to replicate intraluminal pulsatile physiologic flow rate and pressure. For the clot analogs, human blood-derived red blood cells and plasma were mixed to make two types of clot analogs: elastic and fragment-prone. To evaluate the performance of the test bed and compare the three types of phantoms, LVO was replicated in the phantom and thrombectomy procedures using the ADAPT and CAPTIVE techniques were performed by two experienced neurointerventionalists. Results: The 3D-printed phantom is the least expensive and fastest to fabricate, allowing rapid iterations to refine the geometries to make the glass and silicone phantoms. The glass phantom is easier to navigate compared to equivalent anatomy in patients and has the best visualization of the device-clot interaction. The silicone phantom provides the most accurate haptic representation of the navigation of thrombectomy devices in patients, deforming and moving when forces are applied by the device. However, the silicone phantom wall is still significantly more resistant than cerebral arteries and tolerates forces and movements that would be deemed unsafe in clinical situations without tearing. The test bed can generate physiologically realistic pressure. Accurate physiologic pressures with pulsatile waveforms were generated to simulate normotensive (120/80 mmHg) and hypertensive (147/85 mmHg) status. The pressure can be adjusted by the variable flow resistors and tubing length. The clot analogs can be embolized under physiologic flow and consistently lodged at the MCA bifurcation of the cerebrovascular phantoms. Conclusion: The test bed presented in this study is a low-cost, comprehensive, realistic, and versatile platform that enabled high-quality analysis of clot-device interaction. Disclosures: Y. Liu: None. A. Reddy: None. J. Cockrum: None. D. Gebrezgiabhier: None. E. Davis: None. Y. Zheng: None. A. Pandey: None. A. Shih: None. L. Savastano: 4; C; Endovascular Engineering.